A PRODUCTION SCALE BUILD AND DESIGN OF TRASH SKIMMER - Oka Irvianto, Berlian
The waste problems, especially for water waste problem, in Indonesia are serious problems. It is reported that the waste production of Citarum watershed may reach 15,838 tons per day with 15.38% of the production are plastic waste. To reduce that waste production, a device in the form of a boat which is called Trash Skimmer will be designed. From the previous research, a laboratory scaled of Trash Skimmer has been created so that in this research, a production scaled one will be created. In this production scale design, Trash Skimmer will be controlled wirelessly through use of 433 MHz RF wave which is transmitted from transmitter circuit to driver / receiver circuit of Trash Skimmer. The command control of Trash Skimmer that based on the A/D readings of horizontal axis and vertical axis of a joystick and based on the combination of the six buttons will be created. In addition, for controlling the movement of the boat through the propellers, an open looped control system that is based on fuzzy inference system will be created. In this research, the production scale of Trash Skimmer has been built where the transmitter and receiver circuited has been built using printed circuit board (PCB). From the result of the RF communication testing, it is showed that the communication of Trash Skimmer can reach distance of 100 m with a data validity that can reach more than 99%. Furthermore, the Trash Skimmer motion system based on fuzzy inference system with a continuous and varying control surface compared with a system based on classical logic has also been obtained.